Efficacy of latrine promotion on emergence of infection with ocular Chlamydia trachomatis after mass antibiotic treatment: a cluster-randomized trial - Stoller, Nicole E (2011)
The World Health Organization (WHO) recommends environmental improvements such as latrine construction in the integrated trachoma control strategy, SAFE. We report a cluster-randomized trial assessing the effect of intensive latrine promotion on emergence of infection with ocular Chlamydia trachomatis after mass treatment with antibiotics. Twenty-four communities in Goncha Seso Enesie woreda, Amhara Regional State, Ethiopia, were enumerated, and a random selection of 60 children aged 0– 9 years in each was monitored for clinical signs of trachoma and ocular chlamydial infection at baseline, 12 and 24 months. All community members were offered treatment with a single dose of oral azithromycin or topical tetracycline. After treatment, 12 subkebeles were randomized to receive intensive latrine promotion. Mean cluster ocular infection in the latrine and the non-latrine arms were reduced from 45.5% (95% CI 34.1–56.8%) and 43.0% (95% CI 31.1–54.8%) respectively at baseline to 14.6% (95% CI 7.4–21.8%) and 14.8% (95% CI 8.9–20.8%) respectively at 24 months (P=0.93). Clinical signs fell from 72.0% (95% CI 58.2–85.5%) and 61.3% (95% CI 44.0–78.5%) at baseline to 45.8% (36.0–55.6%) and 48.5% (34.0–62.9%) respectively at 24 months (P=0.69). At 24 months, estimated household latrine coverage and use were 80.8% and 61.7% respectively where there had been intensive latrine promotion and 30.0% and 25.0% respectively in the single treatment only arm. We were unable to detect a difference in the prevalence of ocular chlamydial infection in children due to latrine construction.